PPKn Teacher Learning Strategies in Overcoming Lack of Interest in Learning among Students at SMAN 5 Palu - Sukmawati, Sukmawati; Alanur, Shofia Nurun; Jamaludin, Jamaludin; Hidayat, Rahmat; Agustin, Dewi; Kassa, Adriana; Aprizal, Aprizal; Mawar, Mawar; Rani, Kadek Gita; Nurhaliza, Nurhaliza; Amalia, Nur (CV. Rayyan Dwi Bharata, 2025)
This research aims to explore the success of Pancasila and Citizenship Education (PPKn) teachers at SMAN 5 PALU in overcoming students' lack of interest in learning at school. The method used in this research is a qualitative approach by collecting data through observation, interviews and document analysis. The research results show that the learning strategies implemented by PPKn teachers at SMAN 5 Palu, such as the use of good communication, active learning methods, integration of social issues, and use of technology, have succeeded in increasing student involvement in the learning process. By implementing interesting and relevant activities, students feel more motivated to understand the material being taught. Apart from that, students' involvement in extracurricular activities and social projects also contributes positively to their interest in Civics lessons. The conclusion of this research confirms that the success of PPKn teachers at SMAN 5 PALU in making learning interesting and relevant is very important to increase students' interest and motivation to learn. These findings suggest the need for further development of innovative learning methods to support effective citizenship education.